Analisis Perbandingan Kinerja Keuangan Perbankan Indonesia Prapandemi (2018-2019) dan Pascapandemi Covid-19 (2022-2023) - Alviani, Alifia Wida; Vidyasari, Rahmanita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the financial performance comparison of commercial banks listed on the Indonesia Stock Exchange (IDX) during the pre-pandemic period (2018–2019) and post-pandemic period (2022–2023). As a vital part of the financial system, banks faced significant pressure due to the Covid-19 pandemic. A descriptive quantitative approach was used with six financial ratios: NPL, LDR, ROA, ROE, BOPO, and CAR. The sample consisted of 32 commercial banks selected through purposive sampling. Data were analyzed using descriptive statistics, the Paired Sample T-Test, and the Wilcoxon Signed Rank Test. The results showed significant differences in NPL, LDR, BOPO, and CAR ratios, while ROA and ROE showed no significant differences. Overall, the post-pandemic financial performance of banks improved in terms of credit quality, operational efficiency, profitability, and capital strength. These findings indicate that Indonesian commercial banks have managed to recover from the pandemic's impact and are moving toward financial stability.